Female labor supply and parental leave benefits: The causal effect of paying higher transfers for a shorter period of time - Annette Bergemann; Regina T. Riphahn (Institute for Labour Market Policy Evaluation (IFAU), 2009)
We study the labor supply effects of a major change in child-subsidy policy in Germany in 2007 designed to both increase fertility and shorten birth-related employment interruptions. The reform involved a move from a means-tested maternity leave benefit system that paid a maximum of 300 Euro for up to two years to an income dependent benefit system that replaced two third of the pre-birth income for at most one year. As the reform took place very recently, we estimate the labor supply effect by using data drawn from the German Socio-Economic Panel on the intention of women to return to the labor market; notably whether women are likely to return and whether they intend to return quickly. Our results show that the reform yields most of the intended effects: The fraction of mothers who responded that they were going to return to the labor market within a year since the interview increased by 14 percentage points.
Keywords: J13; J21; 330; Female labor supply; fertility; child subsidy; parents money; Elternzeit; Wirkungsanalyse; Frauenerwerbstätigkeit; Arbeitsangebot; Deutschland